2022
DOI: 10.1109/access.2022.3221155
|View full text |Cite
|
Sign up to set email alerts
|

Review on 100% Renewable Energy System Analyses—A Bibliometric Perspective

Abstract: Concerns related to climate change and global warming caused by anthropogenic activities and in particular fossil energy use have been increasing lately. Air pollution and volatile conventional fuel prices emphasize the need to transition the energy system towards very high shares of renewables. 100% renewable energy systems have been analyzed by many researchers starting from 1975. This bibliometric analysis reviews more than 600 scientific articles in which 100% renewable energy systems were surveyed. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 619 publications
0
29
0
Order By: Relevance
“…As of today, a large number of studies, summarised in [8–10], indicate that a 100% RE system can be achieved globally at low cost. Hundreds of studies show the benefit of 100% RE systems [10, 11], which is confirmed for the UK and Ireland by Meschede et al. [12].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…As of today, a large number of studies, summarised in [8–10], indicate that a 100% RE system can be achieved globally at low cost. Hundreds of studies show the benefit of 100% RE systems [10, 11], which is confirmed for the UK and Ireland by Meschede et al. [12].…”
Section: Introductionmentioning
confidence: 86%
“…Compared to other energy system models, it received a high overall rating. LUT‐ESTM was identified as the second most applied tool for investigations of energy system with high shares of renewables, only surpassed by EnergyPLAN [11].…”
Section: Methodsmentioning
confidence: 99%
“…While the energy transition of energy systems to high shares of renewables is well understood, 106,108 the global transition of non-energy feedstocks to 100% renewable feedstock has not yet been investigated in an energy system model. However, it has been conceptionally added to the first energy system model, 109 and it was applied for Europe, 110 which is the only known study applying all required e-fuels and e-chemical buildings blocks for the sustainable energy-industry system transition.…”
Section: Green Chemical Industry In Energy System Modellingmentioning
confidence: 99%
“…However, just 8% of all research on 100% RE are worldwide, 18% are continental and regional evaluations, and 74% are analyses of national or sub-national 100% RE systems. As of the beginning of July 2021 [287], there are 550 recognized items that make up Figure 11. United States (45 articles), Australia (30 articles), Germany (35 articles), Denmark (39 articles), China (17 articles), Italy (10 articles), Sweden (13 articles), Finland (13 articles), Japan (13 articles), Portugal (13 articles), Croatia (11 articles), Spain (11 articles), United Kingdom (14 articles), and Greece are the nations that have been the subject of the most research (10 articles).…”
Section: Global 100% Analysis Of Renewable Energy Systemsmentioning
confidence: 99%